Political Constellation of the Sanggar Kingdom Before Merging with the Bima Kingdom 1901-1926 - Danis, Muhammad; Sukarddin, Sukarddin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The aim of this research is to find out more about the political constellation of the Sanggar kingdom before it joined the Bima kingdom. The research method used is a historical method using a qualitative descriptive approach. This was the success of the Dutch colonial government's diplomacy in its efforts to expand its territory on the island of Sumbawa through an agreement with King Abdullah which was signed on July 16, 1901. We can see the results of this research by the existence of this agreement binding the Sanggar kingdom both in politics, economics and law. so that the economy of the Sanggar kingdom did not make a significant contribution in providing tribute to the Dutch colonial government. Encouraged the Dutch colonial government to merge the Sanggar kingdom into part of the Bima kingdom. In 1926 King Abdullah Syamsuddin Daeng Manggalai signed the handover of the Sanggar kingdom in Bima accompanied by Bumi Tarupong, and the Bima sultanate was represented by Sultan Muhammad Salahuddin accompanied by Bumi Luma Rasanae, Muhammad Yakub and eastern resident officials also witnessed the handover of the Sanggar kingdom to the Bima kingdom.